(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Most students have difficulties in Mathematics subjects. It is an alarming observation that Filipino students excel in knowledge but fare considerably low in lessons requiring high-order thinking skills. Mathematics anxiety results in the negative attitude of students and then makes students deficient in solving mathematical problems. It results in poor performance in solving mathematical problems. This study was conducted to know the challenges encountered of selected Grade 12 General Academic Strand students on Mathematics subject. Quantitative descriptive research was used as the research design for the study. This study attempted to collect quantifiable information to be used for statistical analysis of the population sample and utilized a purposive sampling to select 50 General Academic Strand students to assess the challenges they encountered on the Math subject. With the overall weighted means of 4.04 for female respondents and 3.08 for female respondents, both groups strongly agreed that the strategy, textbooks, and classmate behavior are the common factors of the challenges faced by students on the Math subject. Based on the findings of the study and conclusions, the following recommendation was forwarded. In terms of strategy, students must pay attention when their teachers are giving a lesson on the Math subject. Teachers and school administrators must to not only guide the students but also encourage, inspire, and teach them to be active in discussion and motivate them to do some activity regarding in Mathematics subject for them to love it.